Controlled growth of CuO nanowires on woven carbon fibers and effects on the mechanical properties of woven carbon fiber/polyester composites. (February 2015) - Deka, Biplab K.; Kong, Kyungil; Seo, Jaewoo; Kim, DoYoung; Park, Young-Bin; Park, Hyung Wook
Abstract: The effect of CuO nanowires on the improvement of the mechanical properties of woven carbon fiber (WCF)-based polyester resin composite was studied. The composite was manufactured by the vacuum-assisted resin transfer molding (VARTM) process. CuO nanowires were grown on woven carbon fiber sheets in subsequent steps of seeding followed by growth. Scanning electron microscopy (SEM) showed the growth of CuO nanowires on the surface of the carbon fibers; this growth increased with the number of seeding cycles and the length of the growth time. The concentration of the growth solution did not have a significant effect. The maximum amount of growth occurred for 8 seeding cycles with a 60 mM growth solution and a growth time of 8 h. An analysis of the percent weight change, along with X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy, supported the above findings. The crystalline peak height of the CuO nanowires increased with the nanowire growth. The new absorption peaks arising in the FTIR spectra also indicated growth of CuO nanowires on the WCF. The mechanical properties in terms of tensile strength, modulus, and impact resistance improved significantly after the growth of nanowires on the carbon fibers: the modulus and strength improved by up to 33.1% and 42.8%, while the impact energy absorption increased by 136.8% relative to bare WCF.